In Vitro Evaluation Of Antioxidant Activity Of Flavonoid Compounds From Terong Belanda - Asih, Ida Ayu Raka Astiti; Puspawati, Ni Made; Rita, Wiwik Susanah (Journal of Health Sciences and Medicine; Vol 1 No 2 (2017): JHSM (September 2017), 2018)
Terong belanda (Solanum betaceum, cav), is a fruit that has nutrients and vitamins which are essential for health of human body and it is believed to have a potent antioxidant activity. This research aimed to evaluate in vitro antioxidant activity of flavonoid compounds isolated from Terong belanda. In vitro antioxidant activity was evaluated using DPPH method. Identification of flavonoids was done using Infrared and UV–Vis Spectrophotometers. Extraction of ten (10) kg terong belanda fruits with ethanol gave of 126.17 g peels extract, 178.44 g flesh, and 253.11 g seed extracts respectively. Phytochemical test showed both peels, flesh, and seed extracts of Terong belanda contained flavonoids. Antioxidant activity test showed peels, flesh, and seeds extracts exhibited antioxidant activity with IC 50 of 68,14 ppm, 621.45 ppm, and 1162.608 ppm respectively. Separation and purification of these three active extracts using column chromatography gave each one isolate which positive flavonoid on phytochemical test. Infrared spectra of each isolate from peels, flesh, and seed were similar and each revelaed to contain the same functional groups (OH alcohol, CH aromatic, C=O, C=C, and CH aliphatic). Analysis of UV-Vis spectra and its spectra with shifting reagents of the peels isolates gave absorption at the wavelength range of 310-330 nm (Bans I ) and 245-275 nm (bands II) due to isoflavones group with a hydroxy group at C6, C7 or C7, C8 and C3', C 4 ' while flesh and seed gave absorption at 300-330 nm (bands I) and 275-295 nm (bands II) that indicated the class of flavanones with hydroxyl groups at C-2', C-5', C-6' and Oglycoside at C7 for flessh and hydroxyl group at C6, C7 or C7, C8 for the seed.